THE JOURNALIST IS MARKETING THE NEWS: Social media in the gatekeeping process. (16th November 2016) - Tandoc, Edson C.; Vos, Tim P.
Abstract : This study, based on case studies of three online newsrooms, seeks to understand the patterns of how journalists use social media in their news work. Through 150 hours of observations and interviews with 31 journalists, the study found that journalists are normalizing social media while also reworking some of their norms and routines around it, a process of journalistic negotiation. They are balancing editorial autonomy and the other norms that have institutionalized journalism, on one hand, and the increasing influence exerted by the audience—perceived to be the key for journalism's survival—on the other. In doing so, journalists are also seeing a reworking of their traditional gatekeeping role, finding themselves having to also market the news.